Physical Disturbance Reduces Cyanobacterial Relative Abundance and Substrate Metabolism Potential of Biological Soil Crusts on a Gold Mine Tailing of Central China - Xiao, Jingshang; Lan, Shubin; Zhang, Zulin; Yang, Lie; Qian, Long; Xia, Ling; Song, Shaoxian; Farías, María E.; Torres, Rosa María; Wu, Li (Frontiers in Microbiology, 2022)
As the critical ecological engineers, biological soil crusts (biocrusts) are considered playing essential roles on improving substrate conditions during ecological rehabilitation processes. Physical disturbance, however, often leads to the degradation of biocrusts, and it remains unclear how the physical disturbance affects biocrust microorganisms and the related metabolism. In this study, the photosynthetic biomass (indicated by chlorophyll a), nutrients, enzyme activities and bacterial communities of biocrusts were investigated in a gold mine tailing of Central China, to evaluate the impact of physical disturbance on biocrusts during the rehabilitation process of gold mine tailings. The results showed that physical disturbance significantly reduced the photosynthetic biomass, nutrient contents (organic carbon, ammonium nitrogen, nitrate nitrogen, and total phosphorus) and enzyme activities (β-glucosidase, sucrase, nitrogenase, neutral phosphatase and urease) of biocrusts in the mine tailings. Furthermore, 16S rDNA sequencing showed that physical disturbance strongly changed the composition, structure, and interactions of the bacterial community, leading to a shift from a Cyanobacteria dominated community to a heterotrophic bacteria (Proteobacteria, Actinobacteria and Acidobacteria) dominated community and a more complex bacterial network (higher complexity, nodes, and edges). Altogether, our results showed that the biocrusts dominated by cyanobacteria could also develop in the tailings of humid region, and the dominants (e.g., Microcoleus) were the same as those from dryland biocrusts, nevertheless, physical disturbance significantly reduced cyanobacterial relative abundance in biocrusts. All those results suggest that cyanobacterial inoculation may serve as a promising approach to promote substrate metabolism and accumulation, which would accelerate biocrusts development and the subsequent ecological restoration in mine tailings.